(untitled) (Global Journal of Human-Social Science, 2013)
Expressive creative encounters (ECE) are designed as spaces for the subjects to express and interpret their emotions in the context of social research. The expressiveness of the social subjects has always been a controversial issue for social sciences, because nobody can â€œlive-within-the-otherâ€. But the â€œdevelopmentâ€ and â€œimprovementâ€ of qualitative social research strategies incorporating the â€œexpressiveness capture technologiesâ€ in a progressive yet steady way have been able to bridge the gap between what the researcher sees and what the subject expresses. In this work, creativity is taken as a starting point to produce expressive experiences where individuals "share" and interpret, both with the researcher and with others, in particular social conditions of existence, their sensations and emotions.